THE EFFECTIVITY CURRICULUM 2013 LEARNING OUTCOMES STUDENT SDN 09 HILIA LAMO KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Abdul Istiqlal; Afdhal Rinsik (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
This research was to describe the effectivity curriculum 2013 to learning outcomes student SDN 09 Hilia Lamo kecamatan kamang magek kabupaten agam. This research is guantitative description research. The population research was all student in SDN 09 Hilia Lamo Kecamatan Kamang Magek Kabupaten Agam. The sampel of the research was grade student with total number 30 student. The data of the research were collected by using guentioner. The finding of the research showed that the percentase of high score of really satisfying aspect for always percentage was 64 %. While percentacy aspect satisfying 21 %, percentace aspect less satisfying 15%, and unsatisfying aspect percentage 10 %. Furthermore, the freguency of high score really satisfying aspect for never was 30 respondent. It can be conclude that effectivity curriculum 2013 to learning outcomes student SDN 09 Hilia Lamo kecamtan kamang magek kabupaten agam really satisfying. Bisides, in really satisfying aspect showed that all student in SDN 09 Hilia Lamo kecamatan kamang magek kabupaten agam have really satisfying in learning. Then, the students criteria effectivty curriculum 2013 to learning outcomes student very good.